EDUCATION THOUGHT OF IBNU MISKAWAIH - Asriana Harahap (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2017)
This study aims to know about education based on Ibnu Miskawaih thought. In its analysis, it uses library research approach, analyzing science sources. In this journal, all data are treated and probed from several books, articles, magazines, as well as data from internet which have a relation with the main analysis. Ibnu Miskawaih believes that ethics education is a prime education for human (anna ṣina’ah al-akhlāq afḍal al-shinā’at kullihā), and it is because someone’s ethics can be said as a human (bi tajdīd af’āl al-insān bi mā huwa insān). Education is a process of an establishment process from human’s character towards a virtue, a correction of badness, and improvement process to be better. As Syauqi Beik said in his wisdom words, “Indeed, the people and the nation is very dependent on morals, if good, then the nation will be strong, if it is damaged it will destroy the nation”. It is a strong reason why Ibnu Miskawaih more emphasizes moral education for human development. Literally, human development is soul development with virtue (ahsan taqwīm), it is comparable with physical pleasure, wealth, and power. Human’s life is not life of zuhud and rejection, but it is about compromise and canalization, between body and spirit demands. A Wiseman does not put his priority on world pleasure, but relate it into spiritual pleasure with ethics as the guard. So that, based on Ibnu Miskawaih education thought, he states if someone’s education is higher so his character will be better too.